Low-flow left ventricle percutaneous venting during peripheral veno-arterial extracorporeal membrane oxygenation for the management of transient left ventricle distension. Issue 2 (May 2019) - , Jason E Bloom; , Vincent Pellegrino; , David C McGiffin; Leet, Angeline; Bergin, Peter J
No abstract available